EARLY BABYLONIAN TABLETS IN THE BRITISH MUSEUM'S KUYUNJIK COLLECTION 2 A NEW MANUSCRIPT OF THE COMPOSITION "LETTER FROM SÎN-ŠAMUḪ TO THE GOD ENKI" - Földi, Zsombor J.; Zólyomi, Gábor (2022)
This short paper publishes a new manuscript of the literary composition "Letter from Sîn-šamuḫ to the god Enki" (ETCSL 3.3.19). K.8755 is one of the tablets which proved to be Old Babylonian in spite of their assignment to the British Museum's Kuyunjik Collection. It preserves parts of ll. 8-15 of the composition and probably belonged to a multiple columns tablet. The present paper offers a score transliteration of the lines concerned, based both on the recently published copies and the online photos of the other mss. It provides a number of new readings and interpretations on individual lines.
تنشر هذه الورقة القصيرة مخطوطة جديدة للتأليف الأدبي "رسالة من سين شامو Sîn-šamuḫ إلى الإله إنكي" (ETCSL 3.3.19). K.8755 وهو أحد الرقم التي ثبت أنها بابلية قديمة على الرغم من تخصيصها لمجموعة كيونجيك Kuyunjik بالمتحف البريطاني. وهي تحافظ على أجزاء من ll - 8-15 من التأليف وربما ينتمي إلى رقم به أعمدة متعددة. تقدم الورقة الحالية ترجمة نطقية بالأحرف اللاتينية تظهر تحت النصوص المسمارية المعنية ، تستند بذلك الى كل من النسخ المنشورة مؤخرًا والصورعبرالإنترنت الخاصة بـالمخطوطات الأخرى. فهي بذلك توفر عددًا من القراءات والتفسيرات الجديدة على الأسطر الفردية.